Follistatin-like 1 and its paralogs in heart development and cardiovascular disease - Horak, Martin; Fairweather, DeLisa; Kokkonen, Piia; Bednar, David; Bienertova-Vasku, Julie (Heart failure reviews, 2022)
Cardiovascular diseases (CVDs) are a group of disorders affecting the heart and blood vessels and a leading cause of death worldwide. Thus, there is a need to identify new cardiokines that may protect the heart from damage as reported in GBD 2017 Causes of Death Collaborators (2018) (The Lancet 392:1736-1788). Follistatin-like 1 (FSTL1) is a cardiokine that is highly expressed in the heart and released to the serum after cardiac injury where it is associated with CVD and predicts poor outcome. The action of FSTL1 likely depends not only on the tissue source but also post-translation modifications that are target tissue- and cell-specific. Animal studies examining the effect of FSTL1 in various models of heart disease have exploded over the past 15 years and primarily report a protective effect spanning from inhibiting inflammation via transforming growth factor, preventing remodeling and fibrosis to promoting angiogenesis and hypertrophy. A better understanding of FSTL1 and its homologs is needed to determine whether this protein could be a useful novel biomarker to predict poor outcome and death and whether it has therapeutic potential. The aim of this review is to provide a comprehensive description of the literature for this family of proteins in order to better understand their role in normal physiology and CVD.
Keywords: FSTL5; Animals; biologické markery; Biomarkers; FSTL1; Follistatin-Related Proteins; Fibrosis; lidé; Inflammation; Follistatin; Cardiovascular Diseases; proteiny související s folistatinem; Heart failure; kardiovaskulární nemoci; folistatin; zvířata; fibróza; FSTL4; Humans